2008
DOI: 10.1177/0146167207313727
|View full text |Cite
|
Sign up to set email alerts
|

Self-Objectification and Well-Being in Women's Daily Lives

Abstract: Laboratory experiments and surveys show that self-objectification increases body shame, disrupts attention, and negatively predicts well-being. Using experience sampling methodology, the authors investigated self-objectification in the daily lives of 49 female college students. Building on the predictions of objectification theory, they examined associations between internalizing an observer's perspective on the self and psychological well-being, and examined the moderating roles of trait self-esteem and appea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
99
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 146 publications
(109 citation statements)
references
References 48 publications
(58 reference statements)
8
99
0
2
Order By: Relevance
“…Research demonstrates that women who self-objectify report less negative mood (Fea & Brannon, 2006;Tiggemann & Boundy, 2008) as well as boosts to self-esteem and well-being (Breines, Crocker, & Garcia, 2008;Goldenberg, Cooper, Heflick, Routledge, & Arndt, 2011) when sexually objectified. Indeed, although women are more dependent on men for financial support and protection, men are more dependent on women in the realm of intimate and sexual relations, allowing women to wield some power in heterosexual relationships (Rudman & Glick, 2008).…”
Section: Self-objectification: Power or Palliative?mentioning
confidence: 99%
“…Research demonstrates that women who self-objectify report less negative mood (Fea & Brannon, 2006;Tiggemann & Boundy, 2008) as well as boosts to self-esteem and well-being (Breines, Crocker, & Garcia, 2008;Goldenberg, Cooper, Heflick, Routledge, & Arndt, 2011) when sexually objectified. Indeed, although women are more dependent on men for financial support and protection, men are more dependent on women in the realm of intimate and sexual relations, allowing women to wield some power in heterosexual relationships (Rudman & Glick, 2008).…”
Section: Self-objectification: Power or Palliative?mentioning
confidence: 99%
“…Similarly, as Macmillan et al observed of women's costuming preferences, full disguises are less desirable, in particular because anonymity does not allow the wearer to get "credit" for the ornamental display she feels compelled to exhibit [5]. This is in marked contrast to achievement contexts, where women report downplaying display demands with clothing that conceals (or disguises) the body to regulate other's sexual objectification and their own self-objectifying bodymonitoring [22,23]. It is also in contrast to what how boys approach their costuming.…”
Section: Introductionmentioning
confidence: 99%
“…However, recent research suggests that not all women are negatively affected by self-objectifying situations (Breines, Crocker, & Garcia, 2008). Specifically, levels of self-esteem may be important to consider in understanding the differential effect of self-objectification on well-being.…”
mentioning
confidence: 99%
“…In a diary study examining the role of naturally occurring self-identified self-objectifying situations, Breines et al (2008) demonstrated that individual differences in self-esteem moderated the effect of self-objectification on wellbeing, such that women with high levels of self-esteem experienced higher levels of well-being in self-objectifying situations than their lower self-esteem counterparts. This suggests the possibility that women with high self-esteem might be protected against some of the deleterious consequences of self-objectification.…”
mentioning
confidence: 99%